2012
DOI: 10.1016/j.jpainsymman.2011.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories and Predictors of Symptom Occurrence, Severity, and Distress in Prostate Cancer Patients Undergoing Radiation Therapy

Abstract: Context Radiation therapy (RT) is a common treatment for prostate cancer. Despite available research, prostate cancer patients report that information about side effects is their most important unmet need. Additional research is needed that focuses on specific dimensions of the patient’s symptom experience. Objectives The study’s purposes were to evaluate the trajectories of occurrence, severity, and distress of the six most prevalent symptoms reported by patients undergoing RT for prostate cancer and to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…The occurrence and frequencies of urinary symptoms varied in the literature as well. Most studies reported an increase of urinary symptoms over time (Cameron et al, 2012;Chen et al, 2012;Knapp et al, 2012;McCaughan et al, 2013;Faithfull, 1995;Steginga et al, 2004;Wahlgren et al, 2005), and some reported constant levels of problems during the treatment (Galbraith et al, 2001). Anderson Table 1 Symptoms reported by patients (n ¼ 8), health care professionals (n ¼ 10), and the literature (n ¼ 26).…”
Section: Urinary Symptomsmentioning
confidence: 99%
See 3 more Smart Citations
“…The occurrence and frequencies of urinary symptoms varied in the literature as well. Most studies reported an increase of urinary symptoms over time (Cameron et al, 2012;Chen et al, 2012;Knapp et al, 2012;McCaughan et al, 2013;Faithfull, 1995;Steginga et al, 2004;Wahlgren et al, 2005), and some reported constant levels of problems during the treatment (Galbraith et al, 2001). Anderson Table 1 Symptoms reported by patients (n ¼ 8), health care professionals (n ¼ 10), and the literature (n ¼ 26).…”
Section: Urinary Symptomsmentioning
confidence: 99%
“…In the literature, the most frequently reported symptoms 6 months after the start of radiotherapy were chronic mild to moderate diarrhea and slight to excessive rectal discharge or bleeding (Tsui et al, 2005). Overall, the bowel symptoms increased in severity during the treatment (Chen et al, 2012;Cameron et al, 2012;Knapp et al, 2012;McCaughan et al, 2013) and could remain for quite a long time after cessation of radiotherapy (Galbraith et al, 2001;Steginga et al, 2004;Wahlgren et al, 2005).…”
Section: Bowel Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptom research has so far mostly been performed in a context of the most advanced stages of single diseases (Blinderman et al 2008, Blinderman et al 2009), or in people with an ongoing treatment for a severe disease (Knapp et al 2012, Hofsø et al 2013. Early recognition of and timely response to a chronic disease might lead to a more successful diagnosis and treatment (Vestbo et al 2013, McMurray et al 2012).…”
Section: Symptom Management Modelmentioning
confidence: 99%